Experimental study on single biomolecule sensing using MoS2–graphene heterostructure nanopores. Issue 1 (8th December 2022) - Gu, Chaoming; Yu, Zhoubin; Li, Xiaojie; Zhu, Xin; Jin, Chuanhong; Cao, Zhen; Dong, Shurong; Luo, Jikui; Ye, Zhi; Liu, Yang
Abstract : MoS2 -graphene heterostructure nanopores can prolong the dwell time of BSA molecules up to more than 100 ms compared with other kinds of nanopores. Abstract : Solid-state nanopores play an important role in sensing single-biomolecules such as DNA and proteins. However, an ultra-short translocation time hinders nanopores from acquiring more detailed information about biomolecules, and further applications such as sequencing and molecular structure analysis are limited. Related studies have shown that MoS2 has no obvious impediment to biomolecule translocation while graphene may cause obstacles to this process. By combining these two-dimensional materials, nanopores might slow the biomolecule passage. Herein, we fabricated sub-10 nm ultra-thin MoS2 –graphene heterostructure nanopores with high stability and tested both dsDNA and native protein (BSA) at the single-molecule level in experiments for the first time. Some special signals with advanced order are observed, which may reflect the shape change of the BSA molecules during the slow translocation process. The results show that the translocation time of BSA is slowed down up to more than 100 ms and the signal length and form are determined by the extent of interaction between the BSA and the heterostructure nanopore. The weak interaction between the BSA and the MoS2 layer increases the translocation probability, and meanwhile, the strong interaction of the graphene layer to BSA slows down the translocation and changes its structure. Therefore, our findings indicate the possibilities of slowing down the single-biomolecule translocation and the capability of acquiring more detailed information about biomolecules using MoS2 –graphene heterostructure nanopores.